Spectroscopic methods to quantify molecules of the heme‐biosynthesis pathway: A review of laboratory work and point‐of‐care approaches. Issue 2 (28th February 2021) - Heckl, Christian; Eisel, Maximilian; Lang, Alexander; Homann, Christian; Paal, Michael; Vogeser, Michael; Rühm, Adrian; Sroka, Ronald
Abstract: Spectroscopic methods for quantitative detection of molecules of the heme synthesis and heme metabolism are presented. This can be used to diagnose disease patterns such as iron deficiency, porphyria or free hemoglobin. This article combines an overview of clinical conditions associated with disorders of heme biosynthesis and presents selected laboratory findings in the development of portable diagnostic devices. An iron deficiency measurement device has already been validated as a portable device in clinical trials, two other methods have been tested according to EMA guidelines and are available for use in clinical validation studies. The presented rapid, low‐cost and low‐effort methods can support diagnosis in everyday clinical practice and initiate more targeted therapies, even for rare disease conditions. Abstract : This article combines an overview of clinical conditions associated with disorders of heme biosynthesis and presents selected laboratory findings in the development of portable diagnostic devices. An iron deficiency measurement device has already been validated as a portable device in clinical trials, two other methods have been tested according to EMA guidelines and are available for use in clinical validation studies. The presented rapid, low‐cost and low‐effort methods can support diagnosis in everyday clinical practice and initiate more targeted therapies, even for rare disease conditions. Graphical abstract figure shows schematic representation of heme formation in the mitochondrion and cytoplasm and subsequent erythropoiesis and hemolysis in the vascular system with highlighted key biomarkers